Comparative Analysis of PHP Frameworks for Development of Academic Information System Using Load and Stress Testing - Niarman, Abdurrahman; Iswandi; Candri, Argi Kartika (International Journal Software Engineering and Computer Science (IJSECS), 2023)
There are many programming languages available for the developers to pick when they want to make a web services project such as Java JSP, Python, ASP.Net, PHP and many others. The reason that writer chose PHP as its research topic is that PHP is still being one of the most promising languages especially for developing web services. Several PHP Frameworks are now available on the internet promising that their framework can do better than others. Some popular PHP frameworks are Laravel, Symfony, CakePHP, Yii, and CodeIgniter. Performance is the most aspect to be concerned because of the market’s demands entailing them to do so. The next concern that developer would likely need to decide is whether to go with Pure PHP or to go with PHP Framework. To answer those concerns, this research has been conducted in which a module is taken from an academic information system and will be developed into three similar and equivalent web applications by using Laravel, CodeIgniter, and Pure PHP. The author's aim in conducting this research is to obtain more in-depth information regarding the use of the pure PHP programming language and several frameworks such as CodeIgniter and Laravel. There are many statements stating that using the PHP programming language is no longer feasible, even though in reality using PHP for developing web-based applications is still the choice of many programmers based on statistics from w3tech. The results of research conducted by the author show that the PHP programming language is still very reliable in handling load and stress tests. The pure PHP programming language provides slightly better performance results than the CodeIgniter and Laravel frameworks. Hence, the use of pure PHP or frameworks can be determined from the level of needs of the application development to be created.